2004
DOI: 10.1158/0008-5472.can-04-1978
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based Detection of Multidrug Resistance in Human Tumor Cells by Expression Profiling of ATP-binding Cassette Transporter Genes

Abstract: Different mechanisms of drug resistance, including ATP-binding cassette (ABC) transporters, are responsible for treatment failure of tumors. We developed a low-density DNA microarray which contains 38 genes of the ABC transporter gene family. This tool has been validated with three different multidrug-resistant sublines (CEM/ADR5000, HL60/AR, and MCF7/CH1000) known to overexpress either the ABCB1 (MDR1), ABCC1 (MRP1), or ABCG2 (MXR and BCRP) genes. When compared with their drug-sensitive parental lines, we obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(136 citation statements)
references
References 21 publications
5
130
0
1
Order By: Relevance
“…Although the most frequently selected ABC transporters in various drug resistant cell lines appeared to be ABCB1 and ABCC1, consistent with their known roles in MDR, new roles in drug resistance previously unknown for some ABC transporters were also found using these profiling analyses. For example, ABCC3 and ABCC5 were both found upregulated in the Adriamycin-selected MCF7/AdVp1000 [24] and MCF7/AdVp3000 [40] cell lines using two different arrays, strongly suggesting that these transporters may contribute to Adriamycin resistance. Although these transporters may be selected by verapamil that was present www.cell-research.com | Cell Research Jian-Ting Zhang 321 npg during the selection of these cell lines, the role of ABCC3 in Adriamycin resistance has been validated functionally by the siRNA knock down strategy [40].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the most frequently selected ABC transporters in various drug resistant cell lines appeared to be ABCB1 and ABCC1, consistent with their known roles in MDR, new roles in drug resistance previously unknown for some ABC transporters were also found using these profiling analyses. For example, ABCC3 and ABCC5 were both found upregulated in the Adriamycin-selected MCF7/AdVp1000 [24] and MCF7/AdVp3000 [40] cell lines using two different arrays, strongly suggesting that these transporters may contribute to Adriamycin resistance. Although these transporters may be selected by verapamil that was present www.cell-research.com | Cell Research Jian-Ting Zhang 321 npg during the selection of these cell lines, the role of ABCC3 in Adriamycin resistance has been validated functionally by the siRNA knock down strategy [40].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Eighty-eight such classifiers performed accurately to predict drug sensitivity. Unfortunately, no Table 1 Human ABC Transporters Subfamily Members ABCA ABCA1, A2, A3, A4, A5, A6, A7, A8, A9, A10, A12, A13 ABCB ABCB1, B2, B3, B4, B5, B6, B7, B8, B9, B10, B11 ABCC ABCC1, C2, C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13 ABCD ABCD1, D2, D3, D4 ABCE ABCE1 ABCF ABCF1, F2, F3 ABCG ABCG1, G2, G4, G5, G8 MCF7/AdVp1000 Adriamycin [24] MCF7/AdVp3000 Adriamycin [40] a The functional validation was conducted following identification by array analyses to verify the functional role of the ABC transporter in resistance to corresponding drugs tested. Some ABC transporters have known roles in resistance to the corresponding drugs from prior studies, which are not counted as functional validation in this table.…”
Section: Generation Of Drug Sensitivity Predictors Using Highdensity mentioning
confidence: 99%
See 2 more Smart Citations
“…25 Additionally, recent studies examining ABC transporter gene expression in drug-selected cancer cell lines demonstrated overexpression of a number of transporters not previously recognized as associated with drug resistance (ABCA4, ABCA7, ABCB2, ABCB6, ABCB8, ABCB9 and ABCG1). 26 With the exception of ABCC4, all these transporters are expressed in human CD34 þ 38À hematopoietic cells, again many differentially in comparison to committed progenitors. Together, these data outline the emerging picture that ABC-transporter-mediated protection against xenobiotics and other toxic substrates may be conferred by simultaneous activity of many redundant family members in addition to ABCB1, ABCC1 and ABCG2.…”
Section: Abc Transporter Activity As Marker Of Hematopoietic Stem Cellsmentioning
confidence: 99%